The New International Telecommunication Regulations and the Internet - Hill, Richard. author. aut Link
XVII, 173 p. 3 illus.
Keywords: This book provides a clear and thorough account of the process leading up to the revision of the International Telecommunication Regulations (ITRs) one of the four treaties administered by the ITU. The author’s inside view of the events, and his legal analysis of the new ITRs, are different from that what has been aired in most other accounts to date. His systematic approach shows how much of the criticism of the WCIT-12 process, and of the ITRs themselves, is unjustified. This book provides the most accurate view to date of what the ITRs really mean and of what really happened at WCIT-12, which was undoubtedly a key event in the history of telecommunication policy and which is likely to have significant long-term effects. The book covers in some detail the events leading to the non-signature of the treaty by a significant number of states, outlines possible consequences of that split between states, and offers possible ways forward. The book includes a detailed article-by-article analysis of the new ITRs, explaining their implications, and concludes with recommendations for national authorities. It concludes with an analysis of events from the point of view of dispute resolution theory, offering suggestions for how to avoid divisive outcomes in the future.